Peran Majelis dalam Pemberdayaan Ekonomi di Gereja Toraja Jemaat Imanuel Botang - Markus Sakke Pauranan; Jermia Limbongan (KINAA: Jurnal Kepemimpinan Kristen dan Pemberdayaan Jemaat, 2021)
Abstract: Imanuel Botang congregation had resources both human resources and natural resources that were quite abundant, but had not been managed optimally. Seeing these conditions, researchers were interested in researching the role of church assemblies in the economic empowerment of congregations by focusing research on economic empowerment activities in the field of horticultural agriculture and chicken and pig farming. This research was designed according to qualitative research. Qualitative research aims to find out the role of church assemblies in the economic empowerment of congregations. Data collection techniques were carried out through library research and field research through observation and interview. The study was conducted at the Congregation of Emmanuel Botang from September to November 2020. The results showed the role of the Church Assembly in empowerment is as a consultant and empowerment but this is still not realized because it does not fully understand the duties and vocations as a church assembly, the lack of skills / skills of the church assembly in the field of horticultural agriculture and local village pig and chicken farming, lack of free time and lack of good cooperation.   Keywords:  Economic Empowerment,  Role of the Church Assembly, Toraja Church of Imanuel Botang Congregation  Abstrak: Jemaat Imanuel Botang memiliki sumber daya baik Sumber Daya Manusia maupun sumber daya alamnya yang cukup melimpah, namun belum dikelola secara maksimal. Melihat kondisi tersebut peneliti tertarik melakukan penelitian peran majelis gereja dalam pemberdayaan ekonomi jemaat dengan memfokuskan penelitian pada kegiatan pemberdayaan ekonomi di bidang pertanian hortikultura dan peternakan ayam dan babi. Penelitian ini didesain menurut penelitian kualitatif. Penelitian kualitatif bertujuan untuk mengetahui peran majelis gereja dalam pemberdayaan ekonomi jemaat. Teknik pengumpulan data dilakukan melalui penelitian pustaka dan penelitian lapangan melalui pengamatan (observasi) dan wawancara (interview). Penelitian dilaksanakan di Jemaat Imanuel Botang dari bulan September sampai bulan November 2020. Hasil penelitian menunjukkan peranan Majelis Gereja dalam pemberdayaan adalah sebagai konsultan dan pemberdaya namun hal ini masih belum terealisasi oleh karena belum memahami secara utuh tugas dan panggilan sebagai majelis gereja, minimnya skill/ keterampilan majelis gereja pada bidang pertanian hortikultura dan peternakan babi dan ayam kampung lokal, kurangnya waktu luang dan kurangnya kerja sama yang baik. Kata-kata Kunci: Gereja Toraja Jemaat Imanuel Botang, Pemberdayaan Ekonomi, Peran Majelis Gereja,